Enhanced dielectric properties of MoS2/ PVDF free-standing, flexible films for energy harvesting applications. (March 2023) - Jangra, Mandeep; Thakur, Abhishek; Dam, Siddhartha; Chatterjee, Souvik; Hussain, Shamima
Abstract: Observation of enhanced dielectric constant (∼5 times) in free-standing, flexible composite films of poly(vinylidene fluoride) (PVDF) with the addition of molybdenum disulfide (MoS2 ) nanoflakes, synthesized using sol-gel method, has been reported. The dielectric constant of the composite films varied with the modulation in the filler concentration. At 100 Hz, the dielectric constant of the films with 1 wt% of filler concentration was found to be ∼40. A significant enhancement of ∼900 times in the remanent polarization was also obtained for the same composite film. A triboelectric nanogenerator (TENG) fabricated from a composite film with 1 wt% filler concentration generated an output power of ∼18 µW/cm 2 . Graphical Abstract: ga1 Highlights: Enhancement of ∼40 in the dielectric constant for MoS2/PVDF composite film. Enhancement of ∼900 times in remanent polarization obtained. ∼22 times output power generated of a TENG fabricated of composite film.